1998
DOI: 10.1093/ajcn/68.2.275
|View full text |Cite
|
Sign up to set email alerts
|

Influence of nutritional status on clinical outcome after acute stroke

Abstract: A cause-and-effect relation between protein-energy malnutrition and poor outcome in acute stroke patients has not been definitively established. To measure the effect of the nutritional status of hospitalized stroke patients on clinical outcome, a prospective, observational study was performed. Acute stroke patients admitted to Leicester General Hospital from June 1994 to October 1995 had their nutritional status assessed with anthropometric, hematologic, and biochemical methods within 48 h of admission and af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
193
2
8

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 249 publications
(213 citation statements)
references
References 22 publications
9
193
2
8
Order By: Relevance
“…Serum albumin level was measured within 24 h after stroke onset, and hypoalbuminemia (serum albumin level o35 g/l) was observed in 7.7% of patients. Gariballa et al (1998) found serum albumin concentration o35 g/l in 19% from 201 ischemic stroke patients. In that study, serum albumin level was measured within 48 h after stroke onset.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Serum albumin level was measured within 24 h after stroke onset, and hypoalbuminemia (serum albumin level o35 g/l) was observed in 7.7% of patients. Gariballa et al (1998) found serum albumin concentration o35 g/l in 19% from 201 ischemic stroke patients. In that study, serum albumin level was measured within 48 h after stroke onset.…”
Section: Discussionmentioning
confidence: 97%
“…Hypoalbuminemia was reported in up to 19% of stroke patients (Davalos et al, 1996;Gariballa et al, 1998;Davis et al, 2004). Stroke patients with hypoalbuminemia at admission had increased risk of infective complications (Gariballa et al, 1998;Dziedzic et al, 2006), death (Gariballa et al, 1998;Davis et al, 2004) and poor functional outcome (Davalos et al, 1996;Gariballa et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Many conditions such as malnutrition, liver and kidney diseases may reduce serum albumin concentrations. The catabolic state and the associated neuro-endocrine response that is likely to follow an acute stroke may lead to altered serum albumin concentration and there is recent evidence linking the high stress reaction after stroke and under-nutrition 12 .…”
Section: Discussionmentioning
confidence: 99%
“…In clinical practice serum albumin is often considered as a marker of nutritional status and a negative phase protein that decreases in concentration during injury and sepsis 8 . Serum albumin has neuroprotective effect that is mediated by its multitude of actions including anti-oxidant properties, modulation of endothelial functions and venular perfusion 9 .…”
mentioning
confidence: 99%
“…[16]). Although most clinical studies addressing the impact of PEM on stroke outcome are limited by small sample size and study design, correlations have been drawn between PEM at stroke admission and increased risk of morbidity and mortality [17,18]. A definitive answer was expected from three large Feed or Ordinary Diet Collaboration Trials [19][20][21].…”
Section: Introductionmentioning
confidence: 99%